2020
DOI: 10.3390/e22111260
|View full text |Cite
|
Sign up to set email alerts
|

Time-Delay Characteristics of Complex Lü System and Its Application in Speech Communication

Abstract: Although complex Lü systems have been considered in many studies, application of the self-time-delay synchronization (STDS) of complex Lü systems in secure speech communications does not appear to have been covered in much of the literature. Therefore, it is meaningful to study the STDS of complex Lü systems and its application in secure speech communication. First, a complex Lü system with double time-delay is introduced and its chaotic characteristics are analyzed. Second, a synchronization controller is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Therefore, Chen et al [31] improved Chua circuit using memristor and VOLUME 4, 2016 analyzed its hidden attractor by numerical and experimental methods. Besides, in classical chaotic systems, such as Chen system [32]- [36] , Lorenz system [37]- [39] and Lü system [40]- [42], scholars have also found the possibility of hidden attractor in these systems. Therefore, Lai et al [43] improved some classical chaotic systems, and found that coexistingattractors and hidden attractor exist for some parameter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Chen et al [31] improved Chua circuit using memristor and VOLUME 4, 2016 analyzed its hidden attractor by numerical and experimental methods. Besides, in classical chaotic systems, such as Chen system [32]- [36] , Lorenz system [37]- [39] and Lü system [40]- [42], scholars have also found the possibility of hidden attractor in these systems. Therefore, Lai et al [43] improved some classical chaotic systems, and found that coexistingattractors and hidden attractor exist for some parameter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers achieved the synchronization of the complex Lorenz system and other complex chaotic systems, and adopted them to develop the encryption technology. [14][15][16] From the above discussions, we propose a new communication scheme employing complex parameter modulation and the complex Lorenz system for underwater wireless communication network. We find that there exist large parameter space and parametric attractors in the complex Lorenz system.…”
Section: Introductionmentioning
confidence: 99%